Pollination systems in pioneer trees of the genus macaranga (euphorbiaceae) in Malaysian rainforests - Hashim, Rosli; Maschwitz, U.; Fiala, B.; Meyer, U. (2011)
Many species of Macaranga (Euphorbiacae) are fast-growing pioneer trees with an important role in early succession in south-east Asian rainforests. Within the genus, diverse types of ant-plant associations exist and it has therefore been a model system for studying mutualistic interactions. Little information existed up to now, however, on its reproductive biology. Our comparative study in the genus Macaranga in Sundaland revealed specific flower characteristics and uncommon brood-site pollination systems: enclosed inflorescence morphologies with narrow entrances strongly restrict the set of flower visitors in many species. Thysanoptera were the most abundant insects in 20 of the 26 investigated Macaranga species and, in three species, heteropteran adults and larvae were dominant. Both insect groups used the flower chambers as breeding sites and fed on nectar-producing trichomes inside the bracteoles. Thrips as well as heteropterans are assumed to contribute to pollination. Different Macaranga sections were associated with different flower visitors, suggesting isolation by different pollinators. Thrips pollination and myrmecophyty often occurred in the same sections. The development of enclosed flowers might have facilitated tight ant-plant interactions and prevent ant-pollinator conflicts. However, the complex ecosystems in which the mutualistic systems evolved are rapidly changed with unknown consequences for these specific interactions. (C) 2011 The Linnean Society of London, Biological Journal of the Linnean Society, 2011, 103, 935-953.